Nilai-Nilai Moderasi Beragama dalam Pandangan Buddhis pada Tradisi Nyadran Kuburan di Dusun Depok Kabupaten Temanggung - Ari Mariyono (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to describe the implementation of the Nyadran Kuburan tradition and identify the values of religious moderation contained within it. Using a qualitative approach, the study examines the stages of Nyadran, which involve prayer rituals, mutual cooperation, and communal meals, as well as revealing the spiritual, social, and cultural dimensions within. The study finds that Nyadran Kuburan is not only a religious ritual but also a means to strengthen relationships among residents with different religious backgrounds, while reflecting the practice of religious moderation that can enhance social harmony. The findings are expected to contribute to the preservation of local culture and the development of practical models for implementing religious moderation based on local wisdom in multicultural communities.